Assessing delivered pulse-energies by a nonlinear model - Rabinovitch, Avinoam; Braunstein, Doron; Aviram, Ira; Smolik, Ella; Biton, Yaacov; Rabinovitch, Revital; Thieberger, Reuven (Frontiers in Physics, 2023)
Short-duration and high-amplitude electric pulses have recently been used for two different biological tasks, for stimulating physiological actions such as heart rate or defibrillation and to invoke cell annihilation, as in cancer treatment or atrial fibrillation ablation, by electroporation. However, the physics behind the influence of such pulses has been controversial, due to the linear methods used in the analyses. We present results of a simple nonlinear model to study the situation. Results for the specific nonlinear model show that, below a certain pulse duration, stimulating threshold levels increase rapidly, while the delivered energies reach a lowest plateau, rendering former energy estimates based on linear models, which showed a distinct minimum in the calculated delivered energy at a certain amplitude, invalid for the real nonlinear case.Notably, these results explain the reason why, in pacing, short pulses, of high amplitudes, are more beneficial to the patient than lower and longer ones. However, these pulses should not be too high, since no additional energy reduction is achieved, and electroporation processes could occur.To further reduce the tissue burden, a train of pulses is called for, but delivered energies become higher. Considering this case, we clarify the difficulty to reach threshold at the end of the n'th pulse, for n > 2, and not previously and find the "best" conditions such a train of pulses.